1997
DOI: 10.1108/00242539710177633
|View full text |Cite
|
Sign up to set email alerts
|

Scottish/National Vocational Qualifications: views on the ground

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Much was reported concerning the thoughts of both managers administering the NVQ and employees they are aimed at. Some managers administering the Scottish/National Vocational Qualifications (S/NVQs) for the information and library services (ILS) sector felt that their value to their business was limited (Coker, 1997). Moreover, Coker (1997) believed that S/NVQ jargon deterred potential supporters.…”
Section: Do Nvqs Deliver Business Improvement?mentioning
confidence: 99%
See 2 more Smart Citations
“…Much was reported concerning the thoughts of both managers administering the NVQ and employees they are aimed at. Some managers administering the Scottish/National Vocational Qualifications (S/NVQs) for the information and library services (ILS) sector felt that their value to their business was limited (Coker, 1997). Moreover, Coker (1997) believed that S/NVQ jargon deterred potential supporters.…”
Section: Do Nvqs Deliver Business Improvement?mentioning
confidence: 99%
“…Some managers administering the Scottish/National Vocational Qualifications (S/NVQs) for the information and library services (ILS) sector felt that their value to their business was limited (Coker, 1997). Moreover, Coker (1997) believed that S/NVQ jargon deterred potential supporters. Another manager in the study suggested that some paraprofessional employees preferred the City and Guilds Library and Information Assistants Certificate (LIAC) because it was considered more “academic”, requiring day‐release and examinations (Coker, 1997).…”
Section: Do Nvqs Deliver Business Improvement?mentioning
confidence: 99%
See 1 more Smart Citation